Book Review: Introduction of Selected Chinese and Western Translation Theories - Xu, Jie (Pacific International Journal, 2024)
As China further opens up and integrates into the world, the demand for translation professionals has increased significantly. Despite the development of translation disciplines, the existing teaching materials have not yet met the needs of undergraduate education in terms of quantity and quality, especially for graduate students and doctoral students. To make up for it, the book A Selected Introduction to Chinese and Western Translation Theories emerged at the right moment. This article briefly reviews this translation theory textbook edited by Professor He Xueyun from Hengyang Normal University and published by The Commercial Press in 2021, with the ISBN 9787100201100, using research methods such as literature review, comparative analysis, and case study analysis. The book is divided into three main parts: an introduction to Chinese translation theories, an introduction to Western translation theories, and the main schools of translation theory. It is characterized by its comprehensive content, concise introductions, clear layout, highlighted key points, and ease of self-study, making it an excellent introductory book for learners of translation theory.